EFEKTIVITAS EDUKASI OLEH PERAWAT DALAM MENINGKATKAN PENGETAHUAN IBU TENTANG IMUNISASI DASAR LENGKAP: LITERATURE REVIEW - Syifa Yuhanida Thohir; Miftahul Falah (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
The coverage of Complete Basic Immunisation (IDL) in Indonesia has decreased in several regions, so effective educational intervention is needed to increase the knowledge, attitude, and participation of parents in immunisation programs. Various health education methods, such as booklets, lectures, leaflets, and door-to-door education, have been applied to improve public understanding. This literature review aims to examine the effectiveness of various health education approaches in increasing the knowledge, attitudes, and behaviours of mothers regarding basic immunisation. This literature review was carried out using five scientific articles obtained from Google Scholar with keyword “effectiveness of education”, “Complete immunization”. The research criteria analysed include health education interventions related to basic immunisation, using pre-experimental or quasi-experimental design, and involving mothers who have babies or toddlers. The data was analysed narratively through a comparison of the types of interventions and the main results of each study. From the five journals studied, four of them show that health education is able to significantly increase knowledge. Education using booklets is proven to improve mothers’ knowledge and attitudes regarding complete basic immunisation (p=0.000). Lecture methods and the use of leaflets are also effective in increasing mothers’ knowledge, with leaflets giving the largest increase of 16.36% (p=0,000). The education program from house to house (door to door) also has a good impact in increasing the attitude and awareness of mothers, although there has been no significant increase in immunisation coverage. Health education at Purnama Health Centre has been proven to increase mothers’ knowledge (p<0.001), but has not had a significant effect on immunisation compliance (p=0,232). Meanwhile, the lecture method at the Kaimana Health Centre is also effective in increasing mother’s knowledge with a significance value of p=0.000 of the respondent’s knowledge. The results of the literature show that various health education methods such as booklets, lectures, leaflets, and door to door visits can increase mothers’ knowledge of basic immunisation. However, the increase in this knowledge does not necessarily immediately make the mother more obedient in giving immunisations. Therefore, education is needed that is carried out continuously and support from various parties so that immunisation coverage can be maximised.